PENGARUH TINGKAT INFLASI TERHADAP KINERJA SAHAM SYARIAH JAKARTA ISLAMIC INDEX (JII) DI BURSA EFEK INDONESIA - Nur Khayati Utami Setianingrum; Novita Sari; Retno Indri Yustika (Al-Iqtishad: Jurnal Ekonomi Syariah, 2025)
Inflation is one of the key macroeconomic indicators that plays an important role in influencing economic stability and capital market performance, including the Islamic capital market. The Jakarta Islamic Index (JII), as a leading Islamic stock index in Indonesia, is not immune to the effects of inflation dynamics. This study aims to analyze the effect of inflation on the performance of Islamic stocks listed in the Jakarta Islamic Index (JII) at the Indonesia Stock Exchange. This study employs a quantitative approach using simple linear regression analysis. The data used are secondary data consisting of inflation rates and JII closing prices for the period 2020???2024, obtained from the Central Statistics Agency (BPS) and the Indonesia Stock Exchange (IDX). Data analysis was conducted using SPSS through classical assumption tests, regression analysis, t-tests, and coefficient of determination analysis. The results indicate that inflation has a positive and significant effect on the performance of Islamic stocks in the Jakarta Islamic Index (JII). This is evidenced by a significance value of 0.004, which is lower than the 0.05 significance level. The coefficient of determination (R??) of 0.135 shows that inflation explains 13.5% of the variation in JII stock performance, while the remaining variation is influenced by other factors outside the model. Thus, it can be concluded that inflation is one of the macroeconomic factors affecting Islamic stock performance, although its overall influence remains relatively limited